Continuous ground-based aerosol Lidar observation during seasonal pollution events at Wuxi, China. (April 2017) - Wong, Man Sing; Qin, Kai; Lian, Hong; Campbell, James R.; Lee, Kwon Ho; Sheng, Shijie
Abstract: Haze pollution has long been a significant research topic and challenge in China, with adverse effects on air quality, agricultural production, as well as human health. In coupling with ground-based Lidar measurements, air quality observation, meteorological data, and backward trajectories model, two typical haze events at Wuxi, China are analyzed respectively, depicting summer and winter scenarios. Results indicate that the winter haze pollution is a compound pollution process mainly affected by calm winds that induce pollution accumulation near the surface. In the summer case, with the exception of influence from PM2.5 concentrations, ozone is the main pollutant and regional transport is also a significant influencing factor. Both events are marked by enhanced PM2.5 concentrations, driven by anthropogenic emissions of pollutants such as vehicle exhaust and factory fumes. Meteorological factors such as wind speed/direction and relative humidity are also contributed. These results indicate how the vertical profile offered by routine regional Lidar monitoring helps aid in understanding local variability and trends, which may be adapted for developing abatement strategies that improve air quality. Highlights: Two pollution events are characterized at Wuxi, China from 2013 to 2014. Lidar-derived extinction coefficient and depolarization ratio integrated with air quality and meteorological data are analyzed. Causes of these episodes are seasonally-based: winter haze conceptualizes compound pollution, PM2.5 and O3 are main pollutants in summer.